1999
DOI: 10.1089/hyb.1999.18.305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Anti-HIV-1 Activity of an Anti-p17-Derivative Peptide (P30–52) Monoclonal Antibody

Abstract: The object of this study was to examine the possibility of immunotherapy using anti-human immunodeficiency virus type 1 (HIV-1) p17-derivative peptide monoclonal antibody (MAb), namely MAb 8H10. Previously we established MAb 8H10, and further characterization revealed that it inhibited the viral multiplication of the HIV-1-infected MT-4 cells, and that the inhibitory mechanism related to the decrease of p17 DNA of the infected cells. In the present study, based on the assumption that Hybridoma 8H10 (Hyb 8H10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The MAb was also shown to inhibit cleavage at the p17-p24 site. Another group (13) has shown that MAb to a p17-derived peptide alone inhibits infection of cells by HIV Gag. Taken together, the results suggest that MAbs to Gag cleavage sites in bovine lentiviruses may be further explored for their ability to interact with and/or inhibit different strains of lentiviruses.…”
Section: Discussionmentioning
confidence: 99%
“…The MAb was also shown to inhibit cleavage at the p17-p24 site. Another group (13) has shown that MAb to a p17-derived peptide alone inhibits infection of cells by HIV Gag. Taken together, the results suggest that MAbs to Gag cleavage sites in bovine lentiviruses may be further explored for their ability to interact with and/or inhibit different strains of lentiviruses.…”
Section: Discussionmentioning
confidence: 99%